Pengaruh Media Sosial Tiktok terhadap Motivasi Belajar dan Kemampuan Akademik Siswa di Sekolah Dasar - Andi Fatmawati; Ahmad Ash-Shiddiqy; Noviana Mustapa (Prophetic : Professional, Empathy, Islamic Counseling Journal, 2025)
This study aims to demonstrate the effect of TikTok usage on the level of learning motivation and personal academic abilities of 5th grade elementary school students. This research approach uses of quantitative Ex-post facto research approach. In this study they were 72 fifth grade student respondents from 4 different elementary schools in the Kedaung Kaliangke area, West Jakarta. The data collection technique in this study was a questionnaire and used of Indonesia language subject and mathematics to measure students’ academic abilities with indicators of reading, writing and arithmetic. The result of this study indicate that as many as 92% of respondents have a personal TikTok account and the application is used most often after school (62%) and before going to sleep (53%). As many as 68% of respondents regularly watch TikTok videos for 15-60 minutes per day and 28% of respondents regularly watch TikTok for more than 60 minutes per day. Meanwhile, based on the academic ability test, it was found that the average score of reading ability was 126 words per minute, the average score of writing ability was 27.8 and the average score of arithmetic ability was 4.06.  Thus, based on the Pearson Correlation calculation which states that the p-value (0.722) > 0.05, it can be concluded that there is no significant relationship between the intensity of TikTok use and students' academic abilities.